PELATIHAN MEMBUAT GAME EDUKASI WORDWALL UNTUK GURU DI KELURAHAN KARATON - Listin Rosdiani; Badri Munawar; Ratna Dewi (Jurnal Abdimas Bina Bangsa, 2021)
One of the impacts of the Covid-19 pandemic is changes the learning process in elementary school from offline learning to online learning method. This student community sevice program is the result of observations to elementary school students in the Karaton village, that find the online assigment is boring and unnacttractive. Wordwall has chosen because it can be applied for any subject and helps student to recall the subject so they will not feel bored because they can do the exercises like playing a game. This training activities attended by 8 participants which is a teacher. The activities held in SDN Karaton 3 and consists a stage that is 1). Materials presentation and practicing how to make Wordwall educational game. Data collection technique used questionnaires and data analysis were taken from participant using questionnaires and data analysis were taken from participant response in average. After the training, participants showe positive results that teachers get to know a new knowledge and skill to use wordwall application for online learning method